Financial Self-Sufficiency of Territorial Communities and Provision Mechanisms in Conditions of Decentralization - Kotsiurba, O.Yu.; Sybirtsev, V.V.; Melnyk, T.A. (Управління економікою: теорія та практика, 2023)
The article is paid to the issues of substantiating the expediency of improving the mechanisms for strengthening the financial self-sufficiency of territorial communities and specifying ways to intensify such processes. The thesis proves that extending the powers of local governments to administer local taxes and fees, as well as strengthening the control over their revenues, will help to mobilize additional revenues for local budgets, which are not used for certain reasons. Updating the mechanism of horizontal equalization of the tax capacity of local budgets will minimize the gaps between delegated powers and financial resources. Improving the mechanism of municipal borrowing will help to expand the rights of communities to access investment resources, and normalizing the institutional framework will help to complete the decentralization reform.